Breathing pattern and pulmonary gas exchange in elderly patients with and without left ventricular dysfunction—modification with exercise-based cardiac rehabilitation and prognostic value - Eser, Prisca; Marcin, Thimo; Prescott, Eva; Prins, Leonie F.; Kolkman, Evelien; Bruins, Wendy; van der Velde, Astrid E.; Gil, Carlos Peña; Iliou, Marie-Christine; Ardissino, Diego; Zeymer, Uwe; Meindersma, Esther P.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Inefficient ventilation is an established prognostic marker in patients with heart failure. It is not known whether inefficient ventilation is also linked to poor prognosis in patients with left ventricular dysfunction (LVD) but without overt heart failure. Objectives To investigate whether inefficient ventilation in elderly patients with LVD is more common than in patients without LVD, whether it improves with exercise-based cardiac rehabilitation (exCR), and whether it is associated with major adverse cardiovascular events (MACE). Methods In this large multicentre observational longitudinal study, patients aged ≥65 years with acute or chronic coronary syndromes (ACS, CCS) without cardiac surgery who participated in a study on the effectiveness of exCR in seven European countries were included. Cardiopulmonary exercise testing (CPET) was performed before, at the termination of exCR, and at 12 months follow-up. Ventilation (VE), breathing frequency (BF), tidal volume (VT), and end-expiratory carbon dioxide pressure (PETCO2) were measured at rest, at the first ventilatory threshold, and at peak exercise. Ventilatory parameters were compared between patients with and without LVD (based on cardio-echography) and related to MACE at 12 month follow-up. Results In 818 patients, age was 72.5 ± 5.4 years, 21.9% were women, 79.8% had ACS, and 151 (18%) had LVD. Compared to noLVD, in LVD resting VE was increased by 8%, resting BF by 6%, peak VE, peak VT, and peak PETCO2 reduced by 6%, 8%, and 5%, respectively, and VE/VCO2 slope increased by 11%. From before to after exCR, resting VE decreased and peak PETCO2 increased significantly more in patients with compared to without LVD. In LVD, higher resting BF, higher nadir VE/VCO2, and lower peak PETCO2 at baseline were associated with MACE. Conclusions Similarly to patients with HF, in elderly patients with ischemic LVD, inefficient resting and exercise ventilation was associated with worse outcomes, and ExCR alleviated abnormal breathing patterns and gas exchange parameters.